Risk factors associated with teenage pregnancy: an integrative review (Research, Society and Development, 2020)
Objective: to identify risk factors related to teenage pregnancy. Method: This is an Integrative Literature Review (RIL) type. For data collection, the virtual research libraries were used: Scielo and Lilacs. Results: teenage pregnancy is characterized as a social phenomenon that is debated more in Brazil, as it is seen as a reason for great concern, because in this context there is a diversity of problems that can cause. In the current social panorama it can be defined as a public health problem, because the lack of guidance on sexual education within the family, explaining the various contraceptive methods and what a sexual initiation in that period of the adolescent's life can cause. Conclusion: It is concluded that it is essential at this time of life, to develop educational activities combined with another partnership, joining with other sectors of society such as schools and non-governmental institutions, which can help giving a great help to disoriented adolescents during the period of pregnancy , but it must be considered that the family in this context must be the person's safe haven, and cannot be ignored, playing the role is paramount in the orientation process of these young women.